The New Sentence: June Jordan and the Politics of Parataxis - Kaczmarski, Paweł (Text Matters: A Journal of Literature, Theory and Culture, 2018)
The aim of the paper is to compare and contrast a few select ways in which the poetic use of parataxis can convey a specific political message. Parataxis is understood here broadly, as a certain organizational principle based on a cycle of denarrativization and renarrativization. The first part of the paper reflects on the role the paratactic technique has played within the language of the reactionary populists, both historically and in the recent years. Then, building on the observation that the denarrativized, seemingly „straightforward” nature of the paratactic speech makes it particularly useful for the purposes of right-wing populism, I ask whether parataxis can be reclaimed as a progressive force. In order to answer this question, I go back to some of the issues discussed by Ron Silliman, Fredric Jameson and Bob Perelman in the context of the Language movement and the so-called New Sentence. Here, the work of de- and renarrativization performed as a consequence of the paratactic loosening of conventional textual links and structures is seen as a direct response to the denarrativized nature of everyday life under late capitalism. In the final part of the paper, I contrast the New Sentence parataxis with a more practical, more spontaneous (albeit more conventional) approach embodied by June Jordan. The paratactic structures of her writing remain focused on denarrativization in all of its disruptive and provocative potential, allowing for a certain kind of immediate political intervention.